2005
DOI: 10.1002/jps.20340
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Binding Region (2303–2332) is Involved in Aggregation of Recombinant Human FVIII (rFVIII)**Karthik Ramani and Vivek S. Purohit have contributed equally to this work.

Abstract: Factor VIII (FVIII) is a multi-domain protein that is important in the clotting cascade. Its deficiency causes Hemophilia A, a bleeding disorder. The unfolding of protein domains can lead to physical instability such as aggregation, and hinder their use in replacement therapy. It has been shown that the aggregation of rFVIIII is initiated by small fluctuations in the protein's tertiary structure (Grillo et al., 2001, Biochemistry 40:586-595). We have investigated the domain(s) involved in the initiation of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 39 publications
(40 reference statements)
5
37
0
1
Order By: Relevance
“…This is consistent with our observation that T m is dependent on heating rate, suggesting aggregation kinetics of the protein (42,43). Since the onset of unfolding transition coincides with the formation of aggregates, the effect of PI on stability of FVIII was inferred from the onset of unfolding transition.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with our observation that T m is dependent on heating rate, suggesting aggregation kinetics of the protein (42,43). Since the onset of unfolding transition coincides with the formation of aggregates, the effect of PI on stability of FVIII was inferred from the onset of unfolding transition.…”
Section: Resultssupporting
confidence: 91%
“…Based on biophysical and size exclusion chromatography studies, it has been shown that the onset of transition coincides with the formation of aggregates and the presence of aggregates impacts equilibrium unfolding and T m measurements (42,43). This is consistent with our observation that T m is dependent on heating rate, suggesting aggregation kinetics of the protein (42,43).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A reduction of affinity for PS in the platelet membrane could alter clotting activity. In addition, we have shown that small conformational changes in the lipid-binding region 2303-2332 were responsible for the initiation of the aggregation process (42). Based on these data, we speculate that the N-linked glycosylation proximal to this epitope may play a critical role in the observed loss of activity and aggregation (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…35 Because DCPS binds to the phospholipid binding region, we determined the effect of DCPS on the aggregation behavior of rFVIII using CD under thermal denaturing conditions. Thermal stress was chosen to investigate the effects of DCPS, as it is frequently used to understand protein folding and stability issues.…”
Section: Effect Of Dcps On Thermal Denaturation Of Rfviiimentioning
confidence: 99%